ยานพาหนะจริงแบบย่อส่วนสำหรับการจำลองทางพลศาสตร์ - ปริญญา วัฒนนุกูลชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This research describes a study and development of a scaled vehicle. The scaled vehicle has engineered to have dynamic behaviors equivalent to those of real vehicle. The main purpose is to use the scaled vehicle in a scaling environment interactively with human operator. The scaled vehicle is designed and constructed based on dimensionless analysis and Pl s theorem. Essential parameters are carefully adjusted to have dynamic similarity equivalent with real scaled vehicle. The prototype equipped with sensors, instrument, wireless communication system, controller, and vision on board. Several measurement devices were developed for measuring moment of inertia, and cornering stiffness coefficients. In this work, a 2D dynamic model is applied to predict the behavior of the vehicle. We set up two experiments on the scaled vehicle prototype. We tested the scaled vehicle in skid pad and lane change experiments. The experimental results are provided and discussed. Department